The Evolution of the Agricultural Communications Degree Program at Texas Tech University: A Historical Perspective - Chelsey Ann Aherns; Courtney Gibson (Journal of Applied Communications, 2013)
Texas Tech University’s agricultural communications program began in 1973. Using a historical case study research design, the researchers explored the course offerings, activities, and departmental publications during the previous 40 years. Although the program first offered the agricultural communications option, it took nearly 20 years for an undergraduate degree in this specialization to be made official. This study provides the story of how the program began and how it evolved over time. Other institutions that offer agricultural communications degrees, or are considering this program area, will learn about the gradual development of a lasting program.
Keywords: historical; degree program; agricultural communications; Texas Tech University